Strengths and Weaknesses of Children Witnessing Relatives with Amyotrophic Lateral Sclerosis - Ines Testoni; Lorenza Palazzo; Lucia Ronconi; Tamara Macelloni; Vincenzo Calvo (MDPI AG, 2023)
Research on minors who have a close family member with amyotrophic lateral sclerosis (ALS) is scarce. This study aims to analyze the relationships between reflective function and wellbeing among such children, considering their reflective function, representations of death, and behavioral problems with the following instruments: Reflective Functioning Questionnaire, Testoni Death Representation Scale for Children, Positive and Negative Affect Schedule for Children, and Strengths and Difficulties Questionnaire. Participants were 248 minors divided into the target group (38 children-16 females, 22 males-7-18 years old (M = 11.61, SD = 2.97)) and the control group (210 students-120 females, 90 males 9-14 years old (M = 11.17, SD = 1.33)). Results showed that the target group exhibited more negative affect and hyperactivity. However, they also showed less uncertainty in their mental states. The opportunity to support these minors is discussed.